2
$\begingroup$

Can anyone help to prove or disprove that: for all $a,b>0$ the following inequality holds true?

$${(b-a)^2\over (\log(b)-\log(a))^2}\ge ab$$

I tried to use some convex inequalities such as Jensen inequality but I did not succeed. Can someone provide me with a hint?

$\endgroup$
2
$\begingroup$

Without loss of generality, suppose $b > a$ and $b = λa$, then$$ \frac{b - a}{\ln b - \ln a} = a·\frac{λ - 1}{\ln λ}, \quad ab = λa^2, $$ thus it suffices to prove that$$ \left( \frac{λ - 1}{\ln λ} \right)^2 \geqslant λ, \quad \forall λ > 1 $$ or$$ f(λ) = \frac{λ - 1}{\sqrt{λ}} - \ln λ \geqslant 0. \quad \forall λ > 1 $$

Because$$ f'(λ) = \frac{(\sqrt{λ} - 1)^2}{2λ\sqrt{λ}} > 0, \quad \forall λ > 1 $$ then for any $λ_0 > 1$,$$ f(λ_0) > \lim_{λ \to 1^+} f(λ) = 0. $$

$\endgroup$
5
$\begingroup$

For any $a,b>0$ with $a\neq b$ we have $$ \frac{\log a-\log b}{a-b}=\int_{0}^{+\infty}\frac{dt}{(t+a)(t+b)}$$ which by the Cauchy-Schwarz inequality is bounded by $$ \sqrt{\int_{0}^{+\infty}\frac{dt}{(t+a)^2}\int_{0}^{+\infty}\frac{dt}{(t+b)^2}}=\frac{1}{\sqrt{ab}}.$$ Rearrange and you are done.

$\endgroup$
  • 1
    $\begingroup$ This is an elegant answer thanks. I will definitely take this $\endgroup$ – Guy Fsone Mar 20 '18 at 1:06
4
$\begingroup$

As the inequality is homogeneous and symmetric, it is enough to consider the case $b> a=1$, so we just need to show for $b = x> 1$, $$\left(\frac{x-1}{\log x}\right)^2 \geqslant x \quad \text{or equivalently,}\quad \log x \leqslant \sqrt x - \frac1{\sqrt x}$$

Note by AM-GM, $t+1 \geqslant 2\sqrt t \implies \dfrac{t+1}{2t^{3/2}} \geqslant \dfrac1t \implies $ $$\int_1^x \frac1t dt \leqslant \int_0^x\frac{t+1}{2t^{3/2}} dt\implies \log x \leqslant \sqrt x - \frac1{\sqrt x}$$ Hence proved.

$\endgroup$
1
$\begingroup$

Another simple perspective to this question is to consider the Following Taylor expansion.

We have

$$\begin{align}\frac{(a-b)^2}{ab} &= \frac{a}{b}+\frac{b}{a}-2 = \frac{a}{b}+\left(\frac{a}{b}\right)^{-1}-2\\&= 2cosh\log\left( \frac{a}{b}\right)-2\\ &=-2+2\sum_{k=0}^{\infty}\frac{(\log(a)-\log(b))^{2k}}{2k!} \\ &=(\log(a)-\log(b))^{2}+2\sum_{k=2}^{\infty}\frac{(\log(a)-\log(b))^{2k}}{2k!}\\&\ge \color{blue}{(\log(a)-\log(b))^{2}}\end{align}$$

Given that,

$$ \color{blue}{\frac{e^x-e^{-x}}{2}= cosh x=\sum_{k=0}^{\infty}\frac{x^{2k}}{2k!}. }$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.